Pengaruh Shopping Lifestyle dan Positive Emotion Terhadap Impulse Buying - Pipih Sopiyan; Neny Kusumadewi (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The purpose of this study was to determine the effect of Shopping Lifestyle and Positive Emotion on Impulse Buying both partially and simultaneously. This research is a type of survey research using descriptive and verification approaches. The object of consumer research shop UD Putra Tiga Saudara Majalengka.The results showed that 75.48% of consumers behaved in Shopping Lifestyle, 75.45% of consumers were in Positive Emotion conditions and 75.39% showed impulse buying behavior. Partially Shopping Lifestyle has a positive and significant effect on Impulse Buying with a contribution rate of 13.76%. Meanwhile, Positive Emotion has no effect on Impulse Buying with a contribution rate of 1.88%. However, simultaneous Shopping Lifestyle and Positive Emotion have a significant effect on Impulse Buying with a contribution rate of 15%. Seeing these results, it is important to do research again on the Positive Emotion variable.